Optical fibre characterisation tool - Lau, Jun Kiat (2019)
Optical fibres play an integral role in our society today. In the last few decades, they have replaced common electrical wires for data transmission as they are able to transmit more data at a faster rate over longer distances. Furthermore, they are also incorporated in medicinal imaging and sensory tools like endoscopes. As such with the proliferation of optical fibres in today’s context, there is a need to characterise optical fibres’ light transmitting abilities via two aspects; Numerical Aperture (NA) and Mode Field Diameter (MFD). Optical Fibres can be classified into two categories: Single mode (SM) and Multimode (MM). SM fibres have a small core size (< 10μm) and only one ray of light can be transmitted into it at any time. MM fibres have larger core sizes (62.5/50μm) and allow multiple rays of light to be transmitted at any time. NA is a number that represents the range of angles that a light ray can enter the fibre and be propagated. This only affects MM fibres since only these fibres has a large enough core diameter for light to be coupled into it. MFD represents the area at which light is distributed in the fibre end. Only SM fibres will be affected since they transmit only one ray if light at any point in time, unlike multimode fibres. There will be two experimental set-ups for this project. The first set-up will measure the NA of MM fibres. In this set-up, Light-Emitting Diode (LED) will be used as main light source. The optical fibre that is to be tested in the experiment will be mounted on a rotational stage. The output power from light exiting the tested fibre will be measured via an optical power meter. The output power will vary according to the angle of incidence of the light source. As such in order to reduce abnormalities in the results, LED light has to be coupled into the tested fibre at 90o so that the tested fibre can be rotated accurately to get the range of incident angles. With the data collected, a graph of received power as a function of acceptance angle will be plotted. Half maximum of the full width of the graph will be taken to calculate the NA. A coreless fibre and MM fibre will be used for this experiment. The second experimental set-up will measure the MFD of SM fibres. Technique of near field distribution will be adopted. Once again, LED will be used as the main light source. The optical fibre that is to be tested will be mounted on a stationary mount. Light will be coupled from one end of the fibre to the other end. There will be a Charged Coupled Device (CCD) Camera at the other end of the fibre to capture the beam profile. An imaging software, ImageJ, will be used to analyse the captured profile. The pixel intensity will be measured. A graph of pixel intensity as a function of the beam diameter will be plotted. The MFD will be the diameter where the pixel intensity falls to 1/e2. It can be read off the graph directly. Both experiments were conducted using LED initially. However, due to the inherent nature of LED, the light source was changed to Light Amplification by Stimulated Emission of Radiation (LASER). Both experiments were then run again in order to achieve the intended results.